2016
DOI: 10.1111/dom.12825
|View full text |Cite
|
Sign up to set email alerts
|

Urinary tract and genital infections in patients with type 2 diabetes treated with sodium‐glucose co‐transporter 2 inhibitors: A meta‐analysis of randomized controlled trials

Abstract: The present study found that canagliflozin, dapagliflozin and empagliflozin were associated with a significantly higher risk of genital infections compared with placebo and other active treatments. Only dapagliflozin had a dose-response relationship with UTIs and genital infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
155
0
13

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 196 publications
(173 citation statements)
references
References 53 publications
5
155
0
13
Order By: Relevance
“…The risk of developing genital infections and UTIs is generally increased in patients with diabetes due to changes in immune function and/or inadequate glycemic control . This risk is further increased with the use of SGLT2 inhibitors, likely due to increased glucosuria . The reported incidence of genital infections and UTIs was lower in the present study than in comparable studies in other populations; however, similar results have been reported in other studies of SGLT2 inhibitors in Asian populations .…”
Section: Discussionsupporting
confidence: 78%
“…The risk of developing genital infections and UTIs is generally increased in patients with diabetes due to changes in immune function and/or inadequate glycemic control . This risk is further increased with the use of SGLT2 inhibitors, likely due to increased glucosuria . The reported incidence of genital infections and UTIs was lower in the present study than in comparable studies in other populations; however, similar results have been reported in other studies of SGLT2 inhibitors in Asian populations .…”
Section: Discussionsupporting
confidence: 78%
“…Genital and urinary tract infections were associated with all members of the class and predictable on the basis of the mechanism of action; although the true rate in clinical practice is still uncertain, the high reporting frequency in the postmarketing phase calls for real‐time pharmacovigilance monitoring 50. The overall evidence suggests that SGLT2‐Is increase the risk of genital mycotic infections by four to five times according to the largest MA,51 although they are usually mild to moderate, can be adequately treated with standard medical therapy, and drug discontinuation is not required. Conversely, gathered evidence is not consistent for an increased risk of urinary infections, with MAs showing mixed results 52.…”
Section: Observational Findings: What's Missing?mentioning
confidence: 99%
“…The safety of SGLT2 inhibitors regarding infections of the genital and urinary tracts has been explored in a comprehensive systematic review and network meta-analysis of 52 RCTs involving more than 36,000 patients with type 2 diabetes 33. Based on pooled effect estimates from this study, treatment with canagliflozin 100 or 300 mg resulted in similar rates of urinary tract infections (UTIs), relative to placebo, other individual SGLT2 inhibitors, and other active treatments (including metformin, glimepiride, sitagliptin, saxagliptin, and linagliptin, analyzed as a single control group) 33.…”
Section: Methodsmentioning
confidence: 99%
“…Based on pooled effect estimates from this study, treatment with canagliflozin 100 or 300 mg resulted in similar rates of urinary tract infections (UTIs), relative to placebo, other individual SGLT2 inhibitors, and other active treatments (including metformin, glimepiride, sitagliptin, saxagliptin, and linagliptin, analyzed as a single control group) 33. However, incidence of genital infections was higher for both doses of canagliflozin compared with placebo (OR 4.88 [3.59, 6.64] and 5.23 [3.87, 7.09] for canagliflozin 100 and 300 mg, respectively) and active control (excluding SGLT2 inhibitors) 33. Of note, both the neutral effect of canagliflozin on UTIs and its increased risk for genital infections were also evident in an additional network meta-analysis of 38 RCTs 25.…”
Section: Methodsmentioning
confidence: 99%